Anti-leptospira sp. Antibodies in cats from the semiarid of the Paraíba state - Brasil, A. W. L.; Parentoni, R. N.; Feitosa, T. F. F.; Vilela, V. L. R.; Alves, C. J. A.; Vasconcellos, S. A.; Azevedo, S. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an important zoonosis spread worldwide. The persistence of the agent in the environment and the high potential of infection are guaranteed, among other factors, by the multiplicity of host species able to harbor and eliminate it. On the other hand, the role of cats in the epidemiology of infection has received little attention.